HADIS MENGENDALIKAN AMARAH DALAM PERSPEKTIF PSIKOLOGI - Rovi Husnaini (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
Emotion for each individual has an important role in life. Humans are creatures created by Allah SWT who are equipped with emotions. In the view of psychology, human emotions are divided into two categories, namely, positive emotions and negative emotions. One of the negative emotions angry, the Prophet Muhammad SAW said